EKSISTENSI KEPEMILIKAN TANAH MUSNAH AKIBAT GEMPA BUMI CIANJUR: The Existence of Destroyed Land Ownership Due to the Cianjur Earthquake - Nabilah, Hana Jihan; Setiawati, Anda (AMICUS CURIAE, 2024)
One of the events that caused the elimination of land rights was the destroyed land. The causes of destroyed land are natural disasters such as earthquakes, landslides, and human activities. In the concept of national land law, especially the UUPA, the destruction of land has the legal consequence of erasing land rights. However, according to BPN Regulation Number 17 of 2021, before it is declared as destroyed land, landowners are given priority rights to reclaim/reconstruct their land. The issues raised are what is the status of ownership of land that was declared destroyed due to the earthquake disaster in Cianjur and what is the government's policy in dealing with the problem of land destroyed due to the earthquake disaster in Cianjur. To answer the problem, normative legal research is used which is descriptive-analytical, which is based on secondary data with primary data as complementary data. Data analysis was carried out qualitatively by concluding using deductive logic. With the issuance of Presidential Decree Number 52 of 2022 which has been amended by Presidential Decree Number 27 of 2023 to land owners whose land has been declared destroyed. Spiritual funds are provided as compensation funds given to parties who are entitled to receive spiritual funds. In cases where land was destroyed due to the Cianjur earthquake, the government provided spiritual funds in the form of replacement land and housing. Keywords: Destroyed Land; Spiritual funds; Priority rights; Reconstruction